Improving Science Learning Outcomes Through the Implementation of the Inquiry Learning Model During the Covid-19 Pandemic in Class IX-A Students of SMP Negeri 1 Bendungan for the 2021/2022 Academic Year - Susanto, Edy Elly; Zaya, Amer Shebl (Eduscape : Journal of Education Insight, 2023)
This type of research is Classroom Action Research (CAR). The purpose of this classroom action research (CAR) is to find out how far the improvement of student learning outcomes in science subjects in Fermentation material by applying the Inquiry Learning model. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken it is proven to be able to improve student learning outcomes by achieving the classical mastery that is set at 85%. Classical completeness 73.3% obtained in the first cycle, can be increased in the second cycle to 87%. In terms of student activity, there was also an increase, namely in the first cycle, the moderately active category increased to an active category. The results of this action research show that the implementation of the Covid-19 Learning Period Inquiry Learning Model can improve student learning outcomes in science lessons on electrical. Material with completeness reaching 87 % At the end of cycle II.